2000
DOI: 10.1074/jbc.275.1.624
|View full text |Cite
|
Sign up to set email alerts
|

Altered Regulation of Cardiac Muscle Contraction by Troponin T Mutations That Cause Familial Hypertrophic Cardiomyopathy

Abstract: To study the effect of troponin (Tn) T mutations that cause familial hypertrophic cardiomyopathy (FHC) on cardiac muscle contraction, wild-type, and the following recombinant human cardiac TnT mutants were cloned and expressed: I79N, R92Q, F110I, E163K, R278C, and intron 16(G 1 3 A) (In16). These TnT FHC mutants were reconstituted into skinned cardiac muscle preparations and characterized for their effect on maximal steady state force activation, inhibition, and the Ca 2؉ sensitivity of force development. Trop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
147
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(168 citation statements)
references
References 51 publications
21
147
0
Order By: Relevance
“…The 2.3-fold higher Ca 2ϩ sensitivity in mouse E99K actin-containing thin filaments may be compared with values of 2.0 -2.1-fold with troponin T mutations, measured by IVMA and around 1.5-fold for troponin I mutations measured by ATPase assay (21, 22, 38, 41). The 1.3-fold higher Ca 2ϩ sensitivity of isometric force in ACTC E99K papillary muscle compares with a mean 1.23-fold higher Ca 2ϩ sensitivity observed with a series of seven different HCM mutations in TnI and TnT (21,36,42,43). The increase in Ca 2ϩ sensitivity was less with the human heart E99K actin (1.3-fold), which may reflect the lower mutant actin content compared with the mouse E99K actin (Fig.…”
Section: Actc E99k Mouse Model Of Hcm-we Developed Thementioning
confidence: 94%
“…The 2.3-fold higher Ca 2ϩ sensitivity in mouse E99K actin-containing thin filaments may be compared with values of 2.0 -2.1-fold with troponin T mutations, measured by IVMA and around 1.5-fold for troponin I mutations measured by ATPase assay (21, 22, 38, 41). The 1.3-fold higher Ca 2ϩ sensitivity of isometric force in ACTC E99K papillary muscle compares with a mean 1.23-fold higher Ca 2ϩ sensitivity observed with a series of seven different HCM mutations in TnI and TnT (21,36,42,43). The increase in Ca 2ϩ sensitivity was less with the human heart E99K actin (1.3-fold), which may reflect the lower mutant actin content compared with the mouse E99K actin (Fig.…”
Section: Actc E99k Mouse Model Of Hcm-we Developed Thementioning
confidence: 94%
“…The functional consequences of TnT mutations causing FHC have been extensively characterized (12,17,(25)(26)(27). Previously, our laboratory and others have shown that FHC-causing mutations in TnT predominantly increase myofilament Ca 2ϩ sensitivity (12,25,28).…”
Section: Discussionmentioning
confidence: 99%
“…The experiment is performed after displacement of the endogenous Tn complex and replacement with HCWTnT or TnT mutants and reconstitution with the human cardiac TnI⅐TnC complex. This protocol is well established in this laboratory (12,17,18). Porcine muscle fiber bundles were mounted on a force transducer and treated with the pCa 8.0 relaxing solution containing 1% Triton X-100 for ϳ1 h. The composition of pCa 8.0 solution was 10 Ϫ8 M Ca 2ϩ , 1 mM Mg 2ϩ , 7 mM EGTA, 5 mM MgATP, 20 mM imidazole, pH 7.0, 20 mM creatinine phosphate, and 15 units/ml creatinine phosphokinase; ionic strength ϭ 150 mM.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations